(untitled) (European Journal of Emerging Technology and Discoveries, 2025)
This article budget in organizations financial resources diversification to do and effective management strategies scientific in terms of analysis to do dedicated to . In the article from the budget outside funds of formation main sources , including paid services , public-private partnership projects , grants and sponsorships assistance seeing Uzbekistan under the circumstances budget organizations financial independence in providing face bride problems , in particular , regulatory and legal restrictions , qualifications Insufficiency and transparency issues analysis Improvement roads as legislation reform to do , employees qualification increase , digital management systems current service and service quality improve such as strategies offer Article budget organizations financial stability increase and state to the budget addiction systematic approach to reducing approaches wide illuminates , this and Uzbekistan socio-economic to develop contribution Addictive.